The right doctrine from the wrong texts? essays on the use of ohe Old Testament in the New - Beale, Gregory K. (Grand Rapids, MI Baker, 1994)
Includes bibliographical references and indexes.
Keywords: Bible. N.T. -- relation to the Old Testament; Bible. O.T. -- quotations in the New Testament; Typology (theology).